Some Physicochemical Remarks on Spontaneous Emulsification of Vitreal Tamponades. (15th July 2014) - Costagliola, Ciro; Semeraro, Francesco; dell'Omo, Roberto; Zeppa, Lucio; Bufalo, Gennaro; Cardone, Michele; Romano, Mario; Ambrosone, Luigi
Abstract : The importance of gravitational instability in determining the emulsification of vitreal tamponades is discussed. Theoretical results and numerical simulations indicate that the spontaneous formation of water-silicon oil is a rare event and that the very low concentration of surface active agents cannot justify the systematic formation of emulsions. The gravitational instabilities seem to play the main role. Our theoretical results seem in agreement with the experimental evidences; furthermore they indicate a future research line for the improvement of endotamponades. Indeed, the use of biodegradable antifoam may avoid the formation of bubbles and delay the formation of emulsions.